Risk of COVID-19 Transmission During Gastrointestinal Endoscopy - Rana, Surinder Singh (Journal of Digestive Endoscopy, 2020)
COVID-19 is a viral illness caused by a novel severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2). It is highly contagious virus with human-to-human transmission being primarily attributed to direct contact or air droplets. It is highly infectious and contagious due to high-viable viral loads in the upper respiratory tract secretions of infected patients and also similar viral load being detected in both asymptomatic and symptomatic patients. The virus stability characteristics and modes of transmission via fomites and air droplets make gastrointestinal (GI) endoscopy a high-risk procedure for COVID-19 transmission. This review discusses the currently available literature on risk of transmission of SARS-CoV-2 during GI endoscopy.
Keywords: endoscopy; coronavirus; air droplets; fomites; pneumonia